Exercise augments the modulatory effects of vitamin E on pre-diabetes-induced aortopathy: a potential role of adiponectin. (7th August 2020) - Dallak, Mohammad A.; Al-Ani, Bahjat; El Karib, Abbas O.; Abd Ellatif, Mohamed; Eid, Refaat A.; Al-Ani, Rihab; Mahmoud, Hesham M.; Haidara, Mohamed A.
Abstract: Background: We tested the hypothesis that vitamin E may protect against pre-diabetes-induced aortic injury (aortopathy), and exercise can augment the action of vitamin E. Material and methods: Rats were either fed with a high fat and fructose diet (HFD) (model group) or a standard laboratory chow (control group) for 15 weeks before being sacrificed. The three protective groups were treated with vitamin E (HFD + Vit E), swimming exercises (HFD + Ex), and vitamin E plus swimming exercises (HFD + VitE + Ex), respectively. Results: Aortopathy was developed in the model group as demonstrated by substantial tissue ultrastructural alterations, which were partially protected by vitamin E and effectively protected with vitamin E plus swim exercise. Also, swimming exercises significantly ( p  < .05) increased the modulatory effects of vitamin E on dyslipidemia, insulin resistance, blood pressure, oxidative stress, inflammation, leptin, and adiponectin, except coagulation and thrombosis. Conclusions: Swim exercise augments the protective effects of vitamin E in a pre-diabetic animal model.